2013
DOI: 10.1002/jsfa.6182
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of pigments by addition of surfactants in submerged fermentation of Monascus purpureus H1102

Abstract: The addition of surfactant Triton X-100 could greatly enhance the production of pigment. It was suggested that Triton X-100 facilitated the secretion of intracellular pigment and therefore enhanced pigment production accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 16 publications
(25 reference statements)
5
59
0
Order By: Relevance
“…4a). It has been reported that the lipid cell membrane could be modified in the nonionic surfactant micelle solution, thereby increasing the permeability of cell membrane and the intracellular pigment export in the perstractive fermentation process (Wang et al 2013). In this study, with low pigment content in fermentation broth or mature cells, the intracellular pigments could be completely extracted into the extracellular broth (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4a). It has been reported that the lipid cell membrane could be modified in the nonionic surfactant micelle solution, thereby increasing the permeability of cell membrane and the intracellular pigment export in the perstractive fermentation process (Wang et al 2013). In this study, with low pigment content in fermentation broth or mature cells, the intracellular pigments could be completely extracted into the extracellular broth (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…By using TX as the additive, an enrichment of the hydrophobic pigments occurred upon being “milked” in the artificial nonionic micelle aqueous solution to improve the pigment penetration across the cellular membrane (Hu et al 2012b; Kang et al 2013a). Further study indicated that the nonionic surfactant may modify the cell membrane lipid layer and then improve the rate of secretion of intracellular hydrophobic pigments across the cell membrane (Wang et al 2013). However, the final extracellular pigment concentration is mainly attributed to the solubilization of pigments into the nonionic surfactant micelles and then increasing the concentration gradient between the intracellular and extracellular pigments (Kang et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acid in cell membrane of the mycelia was extracted, purified and methylated according to the method described by Wang et al (2013). After that, the sample dissolved in the n -hexane was collected for GC–MS analysis, using an Agilent 6890 GC (Agilent, Santa Clara, CA, USA) coupled to an Agilent 5973 mass selective detector (MSD) (Agilent, Santa Clara, CA, USA), equipped with a HP-5MS column (5% Phenyl Methyl Silox, 30 m–0.25 mm id 0.25 μm film thickness, Agilent, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Glutamic acid could promote the monacolin K production by regulating the permeability of Monascus mycelium and then the secretion of monacolin K was promoted without feedback inhibition from intracellular product (Zhang et al 2017). The permeability and fluidity of cell membrane depended on the saturability of the containing fatty acid (Wang et al 2013). As high carbon source but low oxidoreduction potential (ORP) could benefit the production of extracellular water-soluble yellow pigments with Monascus ruber CGMCC 10910 (Wang et al 2017), multifaceted mechanisms of high glucose stress that had impacted the metabolism and secretion of Monascus yellow pigments should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Monascus pigment is a natural colorant with many activities (e.g. antibacterial and antioxidant), and it has been considered an ideal replacement for synthetic pigments . Pigment production cannot be further increased using the current liquid fermentation methods, primarily because of feedback inhibition and downstream purification .…”
Section: Introductionmentioning
confidence: 99%